Front-End Activities Promote Front-End Performance?-The Moderating Effect of Front-End Uncertainty (Global Journal of Management and Business Research, 2017)
This study selected Chinese manufacturing parts industry employees as the research object, through questionnaire investigation, empirical analysis of fuzzy front end (FFE) of new product development (NPD) performance mechanism, and focus on the front end performance intermediary role between the two. The FFE activity has a positive effect on the front-end performance; uncertainty between Learning Strategic and front end performance has a negative moderating effect; uncertainty has a negative moderating effect between Stakeholders and involvement front end performance. Uncertainty has a negative moderating effect between Information collection and front-end performance. The research results not only have theoretical implications for the in-depth study of the management of fuzzy front-end activities, but also have important practical significance for the development of the new product development in china.
Keywords: fuzzy front end; new product development; front-end activities; uncertainty; moderating role